The Influence Of Employer Pension Funding Size, Operational Costs, Active Management and Age On Financial Performance - Mansur, Mansur; Mawardi, Wisnu (Politeknik Siber Cerdika Internasional, 2023)
This study aims to analyze the effect of size, operating costs, active management, and the age of Employer Pension Funds on the financial performance of Employer Pension Funds in Indonesia. The population used is the Pension Fund of Employers in Indonesia for the 2017-2021 period by taking samples through purposive sampling. The research method used is a quantitative approach by testing using multiple linear regression analysis in the SPSS program. The source of the data was obtained internally from the OJK and the published results of the JCI daily closing price. The type of data used is secondary data based on the financial reports of Employer Pension Funds and the JCI daily closing price. The results of the study show that the size, operational costs and active management have a negative effect on the financial performance of Employer Pension Funds in Indonesia. Meanwhile, the age of Employer Pension Funds has no effect on the financial performance of Employer Pension Funds in Indonesia